LEGAL PROTECTION OF EMPLOYEES / WORKERS WHO EXPERIENCED EMPLOYMENT RELATIONSHIP IMPACT DIGITALIZATION - Haingo Rabarijaona; Devina Arifani (UNISSULA, 2020)
This journal describes labor problems that arise as a result of technological advances in the modern era, one of which is due to digitalization. This results in termination of employment by employers to workers even without severance pay. The purpose of this paper is to find out how the law regulates the rights and legal protection of workers who have been laid off. The research method used is the normative legal research method. This method examines law normatively by looking at the law from an internal perspective where the object of research is to use legal norms where there is still a vagueness of norms in legal protection for workers due to layoffs due to the impact of this digitization. The final result of this research is that the rights of workers who are laid off are contained in Article 150 to Article 172 of Act No. 13 of 2003 concerning Manpower. Legal protection for workers / laborers due to the impact of digitization is contained in Article 164 Paragraph (3) of the UUK with legal protection in the form of severance pay, awarding money or service fees during the work period of the worker.